2016
DOI: 10.21533/scjournal.v4i2.100
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Genotoxicity Testing Of Vitamin C And Naproxen Sodium Using Plant Bioassay

Abstract: Vitamin C (ascorbic acid) is a water-soluble vitamin and essential for collagen, carnitine and neurotransmitter biosynthesis. Naproxen sodium is propionic acid derivative and anti-inflammatory non-steroid agent. The aim of the study was to assess genotoxicity of selected medicaments and their possible effects on genetic material using Allium bioassay. The treatment of onion bulbs with fresh solutions of Naproxen Sodium (Nalgesin S ®) and Vitamin C was performed using selected concentrations (550, 825 μg/ml and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Our findings regarding mitotic index and chromosomal abnormalities are in agreement with the study reported in Allium cepa by Asita et al, (2017). However, Cenanovic and Durakovic (2016) reported that ascorbic acid treatment at different concentrations (250, 500 and1000 μg/ml) increased the mitotic index in Allium cepa root meristems. It is thought that this difference may have occurred depending on the plant species studied and/or the dose and application time of the ascorbic acid used.…”
Section: Resultssupporting
confidence: 92%
“…Our findings regarding mitotic index and chromosomal abnormalities are in agreement with the study reported in Allium cepa by Asita et al, (2017). However, Cenanovic and Durakovic (2016) reported that ascorbic acid treatment at different concentrations (250, 500 and1000 μg/ml) increased the mitotic index in Allium cepa root meristems. It is thought that this difference may have occurred depending on the plant species studied and/or the dose and application time of the ascorbic acid used.…”
Section: Resultssupporting
confidence: 92%
“…Genotoxic studies on NP are rather scarce, and there is very little information on the potential genotoxic effects of NP despite its wide range of applications, which is mentioned by another author as well [12]. Nevertheless, it has been reported that NP can alter the biochemical biomarkers and genetic materials [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, none of the concentrations of the hyraceum extract tested significantly increased the (P + M)/(A + T) ratio. In a study by Ćenanović and Duraković (2015), treatment of A. cepa root tip cells with 825 μg/ml of ascorbic acid induced a decrease in the frequency of cells in metaphase, anaphase and telophase while the frequency of cells in prophase increased significantly (p < 0.05). Decrease in the number of cells in telophase had no statistical significance.…”
Section: Discussionmentioning
confidence: 96%